2019
DOI: 10.1016/j.solmat.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

MACE nano-texture process applicable for both single- and multi-crystalline diamond-wire sawn Si solar cells

Abstract: MACE nano-texture process applicable for both single-and multi-crystalline diamond-wire sawn Si solar cells .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 69 publications
0
16
0
1
Order By: Relevance
“…However, the MACE-texture currently remains non-optimized from the optics perspective, since the nanostructures are typically polished to enable better conformality, and hence, more efficient surface passivation using chemical vapour deposited (CVD) silicon nitride (SiNx) [4]- [6], which is widely used by the current PV industry. Due to polishing, reflectance of MACE-textured wafers remains as high as 15-30 % without anti-reflection (AR) coatings, and a thick SiNx film is required to reduce reflectance to ~8-10 % [5], [6]. Surface passivation of MACE-structures with lower, <5 % reflectance has been demonstrated with thermally-grown silicon dioxide (SiO2) [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the MACE-texture currently remains non-optimized from the optics perspective, since the nanostructures are typically polished to enable better conformality, and hence, more efficient surface passivation using chemical vapour deposited (CVD) silicon nitride (SiNx) [4]- [6], which is widely used by the current PV industry. Due to polishing, reflectance of MACE-textured wafers remains as high as 15-30 % without anti-reflection (AR) coatings, and a thick SiNx film is required to reduce reflectance to ~8-10 % [5], [6]. Surface passivation of MACE-structures with lower, <5 % reflectance has been demonstrated with thermally-grown silicon dioxide (SiO2) [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The input solar radiation spectrum is assumed to be AM1.5. Both of R and α have tables for their values with each wavelength [21][22][23].…”
Section: B the Optical Model For The Npn Structure Input Solar Radiamentioning
confidence: 99%
“…However, the lithography technique is not suitable for mass production because of its expense, low production-capacity, and incompatibility. Recently, many research interests turn to the metal-assisted chemical etching (MACE) large-area inverted pyramids since the MACE technique is simple, low-cost, large-area, and compatible with the current production line [ 14 , 18 21 ]. For example, Jiang et al [ 7 ] have reported inverted-pyramids nanostructure prepared by the MACE process followed by a post nanostructure rebuilding solution treatment and the conversion efficiency of IPs based multi-crystalline silicon (mc-Si) solar cells in large size of 156 × 156 mm 2 wafers reached up to 18.62%.…”
Section: Introductionmentioning
confidence: 99%